EPR, ENDOR, and electronic structure studies of the Jahn-Teller distortion in an Fe(V) nitride - Cutsail, 3rd, George E; Stein, Benjamin W; Subedi, Deepak; Smith, Jeremy M; Kirk, Martin L; Hoffman, Brian M (Journal of the American Chemical Society, 2014)
The recently synthesized and isolated low-coordinate Fe(V) nitride complex has numerous implications as a model for high-oxidation states in biological and industrial systems. The trigonal [PhB((t)BuIm)3Fe(V)≡N](+) (where (PhB((t)BuIm)3(-) = phenyltris(3-tert-butylimidazol-2-ylidene)), (1) low-spin d(3) (S = 1/2) coordination compound is subject to a Jahn-Teller (JT) distortion of its doubly degenerate (2)E ground state. The electronic structure of this complex is analyzed by a combination of extended versions of the formal two-orbital pseudo Jahn-Teller (PJT) treatment and of quantum chemical computations of the PJT effect. The formal treatment is extended to incorporate mixing of the two e orbital doublets (30%) that results from a lowering of the idealized molecular symmetry from D3h to C3v through strong "doming" of the Fe-C3 core. Correspondingly we introduce novel DFT/CASSCF computational methods in the computation of electronic structure, which reveal a quadratic JT distortion and significant e-e mixing, thus reaching a new level of synergism between computational and formal treatments. Hyperfine and quadrupole tensors are obtained by pulsed 35 GHz ENDOR measurements for the (14/15)N-nitride and the (11)B axial ligands, and spectra are obtained from the imidazole-2-ylidene (13)C atoms that are not bound to Fe. Analysis of the nitride ENDOR tensors surprisingly reveals an essentially spherical nitride trianion bound to Fe, with negative spin density and minimal charge density anisotropy. The four-coordinate (11)B, as expected, exhibits negligible bonding to Fe. A detailed analysis of the frontier orbitals provided by the electronic structure calculations provides insight into the reactivity of 1: JT-induced symmetry lowering provides an orbital selection mechanism for proton or H atom transfer reactivity.